Protocol for a Randomized Trial Comparing Intracranial Pressure Monitor?Based Management of Severe Pediatric Traumatic Brain Injury with Management Based on Imaging and Clinical Examination Without Intracranial Pressure Monitoring - Chesnut, Randall (2023)
BACKGROUND AND OBJECTIVES: Traumatic brain injury (TBI) is a major global public health problem. It is a leading cause of death and disability in children and adolescents worldwide. Although increased intracranial pressure (ICP) is common and associated with death and poor outcome after pediatric TBI, the efficacy of current ICP-based management remains controversial. We intend to provide Class I evidence testing the efficacy of a protocol based on current ICP monitor-based management vs care based on imaging and clinical examination without ICP monitoring in pediatric severe TBI. METHODS: A phase III, multicenter, parallel-group, randomized superiority trial performed in intensive care units in Central and South America to determine the impact on 6-month outcome of children aged 1-12 years with severe TBI (age-Appropriate Glasgow Coma Scale score ?8) randomized to ICP-based or non-ICP-based management. EXPECTED OUTCOMES: Primary outcome is 6-month Pediatric Quality of Life. Secondary outcomes are 3-month Pediatric Quality of Life, mortality, 3-month and 6-month Pediatric extended Glasgow Outcome Score, intensive care unit length of stay, and number of interventions focused on treating measured or suspected intracranial hypertension. DISCUSSION: This is not a study of the value of knowing the ICP in sTBI. This research question is protocol-based. We are investigating the added value of protocolized ICP management to treatment based on imaging and clinical examination in the global population of severe pediatric TBI. Demonstrating efficacy should standardize ICP monitoring in severe pediatric TBI. Alternate results should prompt reassessment of how and in which patients ICP data should be applied in neurotrauma care.